Open-Source Python Scripting and Analysis with Nion Swift - Murfitt, M.F.; Meyer, C.E.; Skone, G.; Dellby, N.; Krivanek, O.L. (Microscopy and microanalysis, 2013)
Extended abstract of a paper presented at Microscopy and Microanalysis 2013 in Indianapolis, Indiana, USA, August 4 – August 8, 2013.